Dependable software engineering : theories, tools, and applications : second International Symposium, SETTA 2016, Beijing, China, November 9-11, 2016, Proceedings /: theories, tools, and applications : second International Symposium, SETTA 2016, Beijing, China, November 9-11, 2016, Proceedings. (2016) - Unknown
No abstract available